Connexin 57 Is Expressed by the Axon Terminal Network of B-type Horizontal Cells in the Rabbit Retina - Pan, Feng (J Comp Neurol, 2012)
In the rabbit retina there are two types of horizontal cell (HC). A-type HCs (AHC) are axonless and extensively coupled via connexin (Cx)50 gap junctions. The B-type HC (BHC) is axon-bearing; the somatic dendrites form a second network coupled by gap junctions while the axon terminals (ATs) form a third independent network in the outer plexiform layer (OPL). The mouse retina has only one type of HC, which is morphologically similar to the B-type HC of the rabbit. Previous work suggested that mouse HCs express Cx57 (Hombach et al. [2004] Eur J Neurosci 19:2633–2640). Therefore, we cloned rabbit Cx57 and raised an antibody to determine the distribution of Cx57 gap junctions among rabbit HCs. Dye injection methods were used to obtain detailed fills for all three HC networks for analysis by confocal microscopy. We found that Cx57 was associated with the B-type AT plexus. Cx57 plaques were anticorrelated with the B-type somatic dendrites and the A-type HC network. Furthermore, there was no colocalization between Cx50 and Cx57. We conclude that in the rabbit retina, Cx57 is only found on BHC-AT processes. Thus, in species where there are two types of HC, different connexins are expressed. The absence of Cx57 labeling in the somatic dendrites of B-type HCs suggests the possibility of an additional unidentified HC connexin in the rabbit.